Das Klima ändert sich. Die Verwaltung auch? Von Beratung bis Partizipation - verändertes Verwaltungshandeln am Beispiel der bayerischen Bergwaldoffensive. - Arzberger, Monika Birgitta (My University, 2019)
Das Bayerische Klimaprogramm 2020 fördert Klimaanpassungsstrategien in Privat- und Körperschaftswäldern. Daher wurde 2008 die „Bergwaldoffensive“ gestartet. Dieses forstpolitische Programm schlägt partizipative Verfahren zur Zielerreichung vor. Die Arbeit zeigt auf, wie die Forstverwaltung diese neue Strategie in ihr Verwaltungshandeln integriert und konkret umgesetzt hat. Ausgehend von einem sozialkonstruktivistischen Paradigma wird der Frage nachgegangen, wie Partizipation als spezifische Interaktionsform aus Verwaltungsperspektive verstanden werden kann.

The Bavarian Climate Program 2020 promotes climate adaptation strategies in private and corporate forests. Therefore the ‘Mountain Forest Initiative’ was started in 2008. This forestry policy program proposes participatory processes for achieving the objectives. This thesis shows how the forestry administration has integrated and implemented this new strategy in its administrative activities. Based on a social constructivist paradigm the question of how participation as a specific form of interaction can be understood from an administrative perspective is examined.
The climate is changing. Administrations as well? New forms of administrative action on the example of the Bavarian ‘Mountain Forest Initiative‘.
Keywords: Forstverwaltung; Landesverwaltung; Verwaltungshandeln; Forstpolitik; Klimawandel; Schutzwald; Landnutzung; Umweltmanagement; Klimaanpassung; Partizipation; Anpassungsstrategie; Organisationskonzept; Befragung; Bergwald